My Facebook for seniors - Miller, Michael 1958- (Que, 2019)
Easy, clear, readable, and focused on what you want to do. Step-by-step instructions for the tasks you care about most Large, full-color, close-up photos show you exactly what to do Common-sense help whenever you run into problems using the Facebook app and website Tips and notes to help you connect with family and friends The full-color, step-by-step tasks-in legible print-walk you through sharing posts, photos, and videos on Facebook. Whether you are new to Facebook or would like to explore more of its features, My Facebook for Seniors makes learning to use the world's most popular social media site simple and fun. The full-color, step-by-step instructions make it easy to connect with family, friends, and colleagues; share digital photos and videos; interact with topic-oriented groups; and much more. Veteran author Michael Miller has written more than 200 nonfiction books and is known for his ability to explain complex topics to everyday readers. Michael wrote this book from the 50+ point of view, using relevant examples and covering all the most popular tasks. Here are just a few things you will learn how to do in this top-selling book: · Sign up for Facebook (it's free!) and create a new account · Use Facebook on your smartphone, tablet, or computer · Configure Facebook's privacy settings to keep your personal information private · Discover how to avoid fake news posted in your News Feed · Find out what you should-and shouldn't-share on Facebook · Find old friends who are also on Facebook · Discover how best to use Facebook to keep in touch with your kids and grandkids · Use the News Feed to discover what your friends and family are up to · Update your friends and family on your current activities.
Includes index. - Description based on online resource; title from title page (Safari, viewed August 27, 2018)
Keywords: Facebook (Electronic resource); Online social networks; Computers and older people; Réseaux sociaux (Internet); Ordinateurs et personnes âgées